2019
DOI: 10.1002/fsn3.1116
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compounds of Hanseniaspora uvarum increase strawberry fruit flavor and defense during cold storage

Abstract: Volatile organic compounds (VOCs) of antagonistic yeasts are considered as environmental safe fumigants to promote the resistance and quality of strawberry ( Fragari a ananassa ). By GC‐MS assays, VOCs of Hanseniaspora uvarum ( H. uvarum ) fumigated strawberry fruit showed increased contents of methyl caproate (5.8%), methyl octanoate (5.1%), and methyl caprylate (10.9%) in postharvest cold storage. Possible mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…For example, our study is supported by past results on Hanseniaspora uvarum, which was shown to be an effective BCA in, e.g., controlling fungal rot in strawberries by biofumigation using VOCs [64]. It reduces the natural development of decay in grapes and strawberries and maintains quality parameters [28,57,65,66].…”
Section: Discussionsupporting
confidence: 84%
“…For example, our study is supported by past results on Hanseniaspora uvarum, which was shown to be an effective BCA in, e.g., controlling fungal rot in strawberries by biofumigation using VOCs [64]. It reduces the natural development of decay in grapes and strawberries and maintains quality parameters [28,57,65,66].…”
Section: Discussionsupporting
confidence: 84%
“…could enhance the activity of defense enzymes in rice [22], tomato [23], and peach [24], etc. There are a few reports showing that bacterial VOC can influence the activity of some defense enzymes of fruit and antioxidant enzymes of plant pathogens significantly [25][26][27]. Although the mechanisms by which microbial antagonists control postharvest diseases have not been clearly elucidated, induced disease resistance has been inferred to be one of the major modes of their actions [4].…”
Section: Discussionmentioning
confidence: 99%
“…Each treatment contained three parallels, and the test was repeated two times. The APX, SOD, CAT, PAL, POD, and PPO enzyme activity was measured as described by Wang L. et al (2019) .…”
Section: Methodsmentioning
confidence: 99%